OP0234 Impact of a Nurse Led Program on the Management of Comorbidities in Rheumatoid Arthritis (RA). Results of a Prospective, Multicentre, Randomized, Controlled Trial (Comedra). (23rd January 2014) - Soubrier, M.; Perrodeau, E.; Gaudin, P.; Cantagrel, A.; Le Loët, X.; Flipo, R.; Guis, S.; Combe, B.; Euller-Ziegler, L.; Schaeverbeke, T.; Fautrel, B.; Saraux, A.; et al.
Abstract : Background: Patients with RA are at an increased risk of developing a number of co-morbid conditions which have a major influence on both mortality and the outcome of RA. Objectives: To evaluate the impact of a nurse led program on the management of comorbidities (cardiovascular diseases (CVD), infection, cancer and osteoporosis) in RA. Methods: Study design : Prospective, randomized controlled open, 6-month trial (NCT #0131652). Patients : RA (ACR 1987 criteria). Study treatment : Collection of data by the nurse at a specific out-patient clinic for the four studied RA comorbidities according to the recommendations of the French Society of Rheumatology. In the event of non-agreement with the recommendation the patient was informed. A report summarizing the results of this program prepared by the nurse was sent to the patient's attending physician and rheumatologist. Treatment allocation : After written informed consent, the study treatment was allocated randomly ( i.e . either this evaluation of comorbidities or an evaluation of a self assessment program (not reported here). Outcome variables : number of actions undertaken against comorbidities according to the recommendations during the 6 months following this program. Actions taken into account for CVD were : introduction of lipid-lowering therapy or anti-platelet therapy, smoking cessation, taking of blood pressure, purchase of a sphygmomanometer, weight loss; for infections: pneumococcal, influenza, hepatitis and meningococcal vaccinations ; for cancers : mammography, Pap smears, consultation with an urologist, fecal occult blood testing, colonoscopy, consultation with a dermatologist; for osteoporosis: dual-Energy X-ray absorptiometry, increased alimentary calcium uptake, introduction of calcium and/or vitamin D supplementation and/or an osteoporotic medication. Results: There was no difference in the baseline characteristics of the 970 recruited patients (488 and 482 in the active and control groups, respectively): Age: 58±11 years, female gender: 79%, disease duration: 11[6.2-19.1] y, history or current biotherapy, DAS28: 3.1 ± 1.3., mHAQ: 0.25 (0.00-0.62). During the 6-month follow-up period, the number of actions per patient was statistically higher in the group comorbidities : 4.54 ± 2.08 vs 2.65 ± 1.57 (p< 0.001); Incidence Rate Ratio(IRR): 1.78 [1.60 -1.83]. This increase concerned CVD (IRR: 1.44 [1.30-1.61]), infections (IRR 1.78 [1.45 – 2.19]), cancer (IRR: 1.65 [1.42 – 1.92]) and osteoporosis (IRR 3.43 [2.88 – 4.13]). Conclusions: This study demonstrates the short-term benefit of a nurse led program on the management of comorbidities. Longer term follow-up of patients is required to better evaluate the sustainability of this benefit. Acknowledgements: This study was conducted thanks to a grant from the French National Research Program (PHRC) and thanks to an unrestricted grant from Roche Ltd France Disclosure of Interest: None Declared